SOCIAL SKILL OF COMMUNITY ORGANIZERS AT BANCEUY TRADITIONAL KAMPONG, SUBANG - Theresia Martina Marwanti; Nenden Rainy Sundary; Benny Setya Nugraha (Politeknik Kesejahteraan Sosial Bandung, 2021)
The purpose of the research is to know how far the social skill of community organizers at anceuy Traditional Community which has special tradition . Community organizers should have skilsl in organizing community such as facilitative and educational skills. The Sub-problematics of the research are facilitative and educational skills of community organizers. The method used is quantitative with descriptive approach. The total respondents are 15 respondents using census technique. Data gathering techniques are questioner. observation and documentation study. Validity test used Pearson Product Moment formula and reliability test used Alpha Cronbach. The result showed facilitative and educational skills at Banceuy traditional Community is good . Facilitative skill is fairly good ,3.23 and educational is good, 2.89. The task and function of community organizers closely related to one of the social functions is helping people to enhance and to use ability effectively to do the life task and solve problem. To run the life task well, community organizers must have good skill. It needs enhancing capacity or training of human resources quality of community organizers.